A gestão hoteleira como prática: experiências sensoriais, estéticas e emocionais no cotidiano organizacional hoteleiro - Brandão, Jammilly Mikaela Fagundes (2019)
This thesis has the general objective of understand the daily practice of management in a hotel. The practice results from a social learning process that reveals the way of "doing", the practical knowledge (knowing-in-practice) of a group, within a situated context, that is repeated and socially recognized by the processes of construction and social reproduction (BISPO, 2013b; GHERARDI, 2012; 2006; ORLIKOWSKI, 2002). The theoretical course of this study is composed of five sections: a) the daily management practice, emphasizing the learning process of managers in the social context b) emotion in the organizational context, presenting and discussing the different theoretical perspectives and emphasizing emotion in managerial practice in light of social construccionism; c) the assumptions, concepts and theoretical and methodological perspectives of the Practice-Based Studies - EBP; d) the use of aesthetics in organizational studies and in managerial practice; and finally, e) an articulation between sensitive knowledge, emotional experiences and managerial practice. Regarding the methodological procedures, this study has a qualitative character and a phenomenological approach. The research was based on the phenomenology of the practice (VAN VANEN, 2014), conducted through the Protocol of Perception of Management Practices - PPPG, of my own creation, which comprises 3 phases: a) the first one refers to the preparation for entry into the field; b) the second, which deals with phenomenological immersion in the field, comprises the shadowing - with the recording of observations and informal conversations in the field diary, and the interviews with the professionals who hold management positions in the hotel under study, inspired by the interview model of Seidman (2006) and based on the guidelines of Van Manen (2014), and c) finally, the third phase consists of the description and analysis of the empirical material, based on the recommendations of Van Manen (2014) on the "phenomenological text", the guidelines of Strati (2007a) on the technique of the "open text" and the considerations of Cloutier (2015) on writing the text. In addition, the "Word Clouds" resource was used to present the results. Considering that this study has as unit of analysis the managerial practice, the managers' workplace configures the context of this research, which is a hotel organization located in Brasília (Distrito Federal – Brazil), belonging to an international hotel chain. Initially, the subjects of the survey were the 8 hotel employees who held management positions: general manager, assistant manager, reception and reservations coordinator, events coordinator, housekeeper, food and beverage coordinator and chef de cuisine. In the second stage of the research (interview) the kitchen chef did not participate, because at this stage of the study she was no longer working in the hotel. The main findings of the study are: a) from the perspective of hotel management as a practice, managerial action is closely associated with the sensory perception and aesthetic judgment of managers; b) managers use their sense organs (eyes, ears, nose, taste and touch) in everyday hotel life in order to maximize the quality of products and services offered in the hotel; c) the hotel management practice is learned in daily work through the development of sensitive knowledge in action; and d) the emotional experiences are part of the organizational daily life and both drive and inhibit the management action. The findings show the links between sensory perceptions, aesthetic judgment, practical knowledge (sensitive and aesthetic) and emotional experiences, aspects inherent to hotel management as a practice. As suggestions for future research, I propose to carry out other studies using the protocol developed in this thesis, aiming to deepen the understanding of hotel management as a practice in hotels of different sizes and organizational structures, as well as, located in other regions, in which other sociocultural contextual elements can be identified, which exert influence on management practice.